Quality of life after treatment for cervical cancer - Rafaella Araújo Correia; Cristine Vieira do Bonfim; Daniela Karina da Silva Ferreira; Betise Mery Alencar Sousa Macau Furtado; Heitor Victor Veiga da Costa; Kéllida Moreira Alves Feitosa; Solange Laurentino dos Santos (Universidade Federal do Rio de Janeiro, 2018)
Abstract Objective: Identify the quality of life of women treated for cervical cancer according to their clinical and socioeconomic characteristics. Methods: This was a analytical study on women who were treated for cervical cancer by means of surgery, radiotherapy and chemotherapy. To evaluate their quality of life, the WHOQOL-bref questionnaire was applied. The Mann-Whitney test was used to investigate associations between domains and variables. Results: There were associations (p < 0.05) between the WHOQOL-bref domains and the variables of income, conjugal situation, leisure activities and treatment undergone. The physical and psychological domains were associated with overall quality of life (R = 0.54 and R = 0.63, respectively). Conclusions: Socioeconomic conditions and the type of treatment undergone influenced the quality of life of these women after their treatment. There is a need to increase the reach of cervical cancer screening among women who are less economically favored; and, after treatment, to offer alternative measures that soften the secondary effects.